Affinity Chromatography of Native and Recombinant Proteins from Receptors for Insulin and IGF-I to Recombinant Single Chain Antibodies - Fujita-Yamaguchi, Yoko (Frontiers in Endocrinology, 2015)
Affinity chromatography is an efficient method to isolate proteins by taking advantage of their affinities for specific molecules such as substrates, inhibitors, antigens, ligands, antibodies, and other interacting molecules including subunits. Nowadays, we take the effectiveness and excellence of this technology for granted. This essay will mainly cover the use of affinity chromatography based on my experience.